A Multilocus Approach to Understanding Historical and Contemporary Demography of the Keystone Floodplain Species Colossoma macropomum (Teleostei: Characiformes) - Santos, Maria da Conceição Freitas; Hrbek, Tomas; Farias, Izeni P. (Frontiers in Genetics, 2018)
We studied the natural populations of a flagship fish species of the Amazon, Colossoma macropomum which in recent years has been suffering from severe exploitation. Our aim was to investigate the existence or not of genetic differentiation across the wide area of its distribution and to investigate changes in its effective population size throughout its evolutionary history. We sampled individuals from 21 locations distributed throughout the Amazon basin. We analyzed 539 individuals for mitochondrial genes (control region and ATPase gene 6/8), generating 1,561 base pairs, and genotyped 604 individuals for 13 microsatellite loci obtaining, on average, 21.4 alleles per locus. Mean HE was 0.78 suggesting moderate levels of genetic variability. AMOVA and other tests used to detect the population structure based on both markers indicate that C. macropomum comprises a single and large panmitic population in the main channel of the Solimões-Amazonas River basin, on the other hand localities in the headwaters of the tributaries Juruá, Purus, Madeira, Tapajós, and localities of black water, showed genetic structure. The greatest genetic differentiation was observed between the Brazilian Amazon basin and the Bolivian sub-basin with restricted genetic flow between the two basins. Demographic analyzes of mitochondrial genes indicated population expansion in the Brazilian and Bolivian Amazon basins during the Pleistocene, and microsatellite data indicated a population reduction during the Holocene. This shows that the historical demography of C. macropomum is highly dynamic. Conservation and management strategies should be designed to respect the existing population structure and minimize the effects of overfishing by limiting fisheries C. macropomum populations.